Optimalisasi Pengelolaan Hipertensi Berbasis Komunitas melalui Pendekatan Keluarga untuk Meningkatkan Kesehatan Masyarakat - Endriyana, Titha; Salsabila, Anisa Aulia; Amalia, Risa Putri; Yulianita, Vika; Magvirah, Puja; Sadri, Khofifah Yuniarsih; Luthfiyanti, Salzabila Ulfa; Hapsari, Fika Veny; Khairunnisa, Khairunnisa; Dumat, Valentino Ardana; Rahmadani, Ferdi; Widyastuti, Dwi (Universitas Pahlawan Tuanku Tambusai, 2025)
Hypertension is a non-communicable disease that is a major public health concern worldwide. Although the disease often causes no symptoms, it has a high risk of causing serious complications. This study aims to optimize community-based hypertension control using a family approach that can improve community awareness and well-being. Lifestyle changes, health education, and regular blood pressure monitoring were the tactics used. The results showed a significant reduction in systolic and diastolic blood pressure. The study also showed an increase in community understanding of hypertension risk factors from 40% to 85% and an increase in adherence to a healthy lifestyle to 78%. Family involvement in health monitoring has shown that this helps them control hypertension. The results of this study suggest that family-based strategies may be effective for preventing and controlling hypertension in the community.